Anchors of identity: Integrating maritime heritage into Singapore's urban authenticity - Saifudeen, Izzah Sarah Binte Omer Ali (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Singapore’s identity as a global city is deeply intertwined with its maritime history, yet its urban narratives often prioritize land-based development over maritime heritage. This paper explores the integration of Singapore’s maritime legacy into the concept of City Authenticity, arguing that maritime heritage sites, such as jetties, harbors, and kelongs, are vital cultural anchors that sustain a more authentic urban identity. Methods: Using a mixed-methods approach combining ethnographic observations, interviews, and archival research, the study examines the historical, cultural, and communal values of these spaces. Findings: Findings reveal a significant gap between public recognition of maritime heritage and its representation in conservation policies, which are skewed towards urban structures. Conclusion: The paper proposes a Maritime Heritage Conservation Framework, merging existing conservation criteria with marine-specific considerations, emphasizing historical significance, communal engagement, and aesthetic integration. The framework also suggests innovative educational tools, including digital exhibits and interactive programs, to reconnect younger generations with Singapore’s maritime roots. By aligning these efforts with the broader discourse on City Authenticity, the study underscores the potential of maritime heritage to balance modernization with cultural continuity. Ultimately, the research advocates for a holistic and inclusive approach to urban conservation that values maritime heritage as a cornerstone of Singapore’s national and urban identity. Novelty/Originality of this article: This study offers a novel perspective on integrating Singapore's maritime heritage into the concept of City Authenticity, proposing a Maritime Heritage Conservation Framework to bridge the gap between urban development and cultural preservation.